A comparative study of chitosan and poloxamer based thermosensitive hydrogel for the delivery of PEGylated melphalan conjugates. (2nd December 2015) - Alexander, Amit; Saraf, Swarnlata; Saraf, Shailendra
Abstract: Objective : Although the melphalan (ML) used extensively for the management of breast cancer, its clinical application is limited due to significant hemolytic activity. In the present work, a comparative analysis of two distinct in situ -based thermogelling polymers of PEGylated ML was performed. Methods : Briefly, the PEGylated conjugate of the melphalan (MLPEG 5000) for local and sustained drug release action is loaded into two different thermogelling polymeric systems, namely chitosan- and poloxamer-based systems. The synthesized conjugate was loaded to a chitosan (MLP 5000) and poloxamer-based (MPX-CG) thermogelling injectable hydrogels. These thermogelling hydrogels were evaluated for in vitro hydrolysis, in vitro hemolytic activity. and in vitro anticancer activity. Results : The lower percent cumulative hydrolysis was witness for both the hydrogels. MPX-CG and MLP 5000 hydrogels as predicted had shown lower percent cumulative hydrolysis of 3.31 ± 0.1 and 1.67 ± 0.1 after 6 h. The percentage hemolysis of MPX-CG and MLP 5000 even at a concentration of 32 µg/ml was found to be 39.23 ± 1.24% and 34.23 ± 2.24%, observed at 1 h, respectively. Both the hydrogels showed similar anticancer pattern, the MPX-CG hydrogel showed low cell viability of 8.4 ± 1.1% at a concentration of 150 µM and the MLP-5000 hydrogel showed slight higher cell viability (13.12 ± 5.4%) as compared with MPX-CG hydrogel. Conclusion : Hence, from the present study it can be well understood that both the chitosan- and the poloxamer-based thermogelling hydrogel proves to be an effective drug delivery systems for the delivery of the PEGylated conjugates.